Myth of Romani Music in Prague - Jurková, Zuzana (Lidé města, 2009)
In today’s Prague one can find a great variety of musical events and recordings labeled as Romani/Gypsy music – from classical music with “Gypsy” themes to romano hip hop. For meaningful understanding and organization of it, the article uses both the basic ethnomusicological model of Alan P. Merriam (1964) and Kay Kaufman Shelemay’s (2006) concept of soundscapes. With their help, four “musical worlds” – soundscapes – are presented: the romantic image that non-Roma have of Roma; Romani coffee house bands; traditional Romani bašaviben, that is, playing for their own entertainment, influenced by popular music; and emerging Romani hip hop. Each of these worlds – however they influence each other – is at the same time internally coherent and thus it is easy to follow the connections among the original purpose of this type of music, the behavior of the musicians and the public, and musical sound.